Mitotically Active Leiomyoma of the Uterus in a Postmenopausal Breast Cancer Patient Receiving Tamoxifen - I-Feng Liu; Yu-Shan Yen; Ya-Min Cheng; Cheng-Yang Chou (Elsevier, 2006)
Objective: Mitotically active leiomyoma of the uterus complicated with postmenopausal vaginal bleeding has never been reported in Taiwan. Here, we present a case of mitotically active leiomyoma of the uterus complicated with postmenopausal vaginal bleeding in a breast cancer patient who had been receiving tamoxifen for 2 years Case Report: A 56-year-old woman visited our clinic due to abnormal vaginal spotting for 3 months. This patient had been menopausal for about 6 years without hormone replacement therapy. She had been suffering from breast cancer, had undergone conservative breast surgery, and had been taking tamoxifen (20 mg/day) for 2 years. Pelvic ultrasound was performed and revealed an 8.9 ×7.7 cm uterine mass. After simple total hysterectomy, we found an enlarged uterus with a mass over the posterior wall. Final pathology demonstrated a mitotically active leiomyoma, adenomyosis of the uterus, and proliferation of the endometrium. Conclusion: Endometrial cancer is rarely noted in breast cancer patients taking tamoxifen. Further, none have reported mitotically active leiomyoma of the uterus. From this case, endometrial proliferation and mitotically active leiomyoma of the uterus may be related to tamoxifen therapy, and should not be neglected in breast cancer patients.